Extended studies of interspecific relationships in Daucus (Apiaceae) using DNA sequences from ten nuclear orthologues - Martínez Flores, Fernando; Crespo, Manuel B.; Geoffriau, Emmanuel; Allender, Charlotte; Ruess, Holly; Arbizu Berrocal, Carlos Irvin; Simon, Philipp W.; Spooner, David M. (Oxford University, 2020)
Daucus has traditionally been estimated to comprise 21–25 species, but a recent study expanded the genus to c. 40 species. The present study uses ten nuclear orthologues to examine 125 accessions, including 40 collections of 11 species (D. annuus, D. arcanus, D. decipiens, D. durieua, D. edulis, D. gracilis, D. minusculus, D. montanus, D. pumilus, D. setifolius and D. tenuissimus) newly examined with nuclear orthologues. As in previous nuclear orthologue studies, Daucus resolves into two well-defined clades, and groups different accessions of species together. Maximum likelihood and maximum parsimony analyses provide concordant results, but SVD quartets reveals many areas of disagreement of species within these two major clades. With maximum likelihood and maximum parsimony analyses Daucus montanus (hexaploid) is resolved as an allopolyploid between D. pusillus (diploid) and D. glochidiatus (tetraploid), whereas with SVD quartets it is resolved as an allopolyploid between D. glochidiatus and an unknown Daucus sp. We propose the new combination Daucus junceus (Durieua juncea) for a neglected species endemic to the south-western Iberian Peninsula often referred to as D. setifolius, and we place D. arcanus in synonymy with D. pusillus. Three lectotypes are also designated.